Sandra needs a new bicycle tire. Her tire has a circumference of about 113,04 inches. What is the radius of her tire?

Question

Sandra needs a new bicycle tire. Her tire has a circumference of about 113,04 inches. What is the radius of her tire?

in progress 0
RuslanHeatt 6 months 2021-08-05T22:12:36+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-08-05T22:14:25+00:00

    Answer:

    113,04 square root is 10.632027088 divided by Pi

    3.38427933228

    so the radius of her tire is 3.38

    Hope This Helps!!!

    0
    2021-08-05T22:14:32+00:00

    Answer: 18 inches

    Step 1: Write equation

    To find the radius, we will go through the formula for the circumference. Let’s write the example equation now.

    C= 2πr

    Step 2: Substitute numbers

    Now we can write the full equation, using the information from the question. The r will be the only number to stay the same, as we ar s working to find the radius. Let’s substitute the C in the equation for 113.04 as given in the equation.

    C= 2πr
    113.04= 2πr

    Step 3: Solve

    For step 3, we can solve the equation. Let’s start by rewriting the equation.

    113.04= 2πr

    Now let’s multiply what is available on the right side. This would be 2 and pi. For the sake of the equation, pi will be rounded to 3.14.

    113.04= 2πr
    113.04= 2•3.14•r
    113.04= 6.28r

    Now let’s work to get r alone on the right side. We can do so by dividing each term by 6.28, on both the left and right side.

    113.04= 6.28r
    113.04/6.28= 6.28r/6.28
    18= r

    This is your answer! To be sure, let’s check our answer in the final step.

    Step 4: Check

    To ensure that we got the right answer, let’s rewrite the original formula, and solve it to see if the answer is the same on the left and right side.

    C= 2πr
    113.04= 2•3.14•18
    113.04= 6.28•18
    113.04= 113.04

    Our answer is correct. 18 inches is the length of the radius. Hope this helps! Comment below for more questions.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )